In Search of the Auditory, Phonetic, and/or Phonological Problems in Dyslexia: Context Effects in Speech Perception. - Blomert, Leo; Mitterer, Holger; Paffen, Christiaan (Journal of Speech, Language & Hearing Research, 2004)
There is a growing consensus that developmental dyslexia is associated with a phonological-core deficit. One symptom of this phonological deficit is a subtle speech-perception deficit. The auditory basis of this deficit is still hotly debated. If people with dyslexia, however, do not have an auditory deficit and perceive the underlying acoustic dimensions of speech as well as people who read normally, then why do they exhibit a categorical-perception deficit? A potential answer to this conundrum lies in the possibility that people with dyslexia do not adequately handle the context-dependent variation that speech signals typically contain. A mathematical model simulating such a sensitivity deficit mimics the speech-perception deficits attributed to dyslexia. To assess the nature of the dyslexic problem, the authors examined whether children with dyslexia handle context dependencies in speech differently than do normal-reading individuals. Contrary to the initial hypothesis, children with dyslexia did not show less context sensitivity in speech perception than did normal-reading individuals at auditory, phonetic, and phonological levels of processing, nor did they reveal any categorization deficit. Instead, intrinsic properties of online phonological processes, not phonological representations per se, may be impaired in dyslexia. Reprinted by permission of the publisher.